Indikasi Bullying Fisik pada Siswa SD dan Implikasinya Terhadap Pendidikan Akhlak Menurut Tuntunan Agama - Kurnia, Dadang; Aeni, Ani Nur (Universitas Pendidikan Indonesia, 2018)
Cases of bullying among elementary school students are high. Therefore, it needs to get attention. This study reveals an indication of physical bullying that occurs in elementary students and its implications for moral education according to the guidance of Religion. The method used is survey and literature study with the qualitative approach. Participants involved a number of 55 elementary school teachers in Cirebon district and the city of Cirebon. The results showed that: 1) almost half of the physical bullying indication occurred in primary school with the highest percentage is in punching and pinching behavior, while the smallest percentage is strangling behavior; 2) moral education can be a therapy to change the bad behavior of physical bullying and can be used as a preventive effort.